DEVELOPING ENGLISH-OPOLY GAME AS A MEDIUM TO TEACH THE 8TH GRADERS SPEAKING RECOUNT TEXT (RETAIN, 2014)
DEVELOPING ENGLISH-OPOLY GAME AS A MEDIUM TO TEACH THE 8TH GRADERS SPEAKING RECOUNT TEXT Agnesia Gita Flamboyan English Department, Faculty of Languages and Arts, State University of Surabaya gita.flamboyan@yahoo.com Lies Amin Lestari English Department, Faculty of Languages and Arts, State University of Surabaya lies.aminlestari@yahoo.com Abstrak Berbicara dianggap sebagai keterampilan yang paling sulit dalam belajar Bahasa Inggris. Observasi awal yang dilakukan di SMP 1 Ngoro menunjukkan bahwa para siswa mempunyai kemampuan yang baik dalam mengerti pelajara, namun mereka selalu ragu untuk berbicara. Para siswa membutuhkan suasana yang santai untuk belajar Bahasa Inggris di dalam kelas. Berbicara teks recount tidak bisa hanya dilakukan dengan mengerti struktur umumnya saja, tetapi juga perlu latihan untuk mengungkapkannya. Oleh karena itu, permainan modifikasi seperti English-opoly dibutuhkan sebagai media baru untuk membantu para siswa berbicara teks recount dengan cara yang menyenangkan. Karena permainan membuat suasana menyenangkan dan santai (Uberman, 1998). Penelitian ini menggunakan model R & D oleh Borg dan Gall untuk mengubah permainan monopoli biasa menjadi permainan bernama English-opoly yang digunakan untuk mengajar siswa kelas 8 berbicara teks recount. Selain itu, penelitian ini juga untuk mengetahui respon siswa terhadap permainan yang dikembangkan tersebut. Validasi ahlis menunjukkan bahwa game ini cocok untuk membantu siswa mencapai tujuan pembelajaran. Game ini juga memenuhi criteria sebagai permainan yang baik untuk digunakan sebagai media pembelajaran. Selanjutnya data dari observasi dan wawancara menunjukkan bahwa sebagian besar siswa memberikan respon yang baik dan setuju bahwa English-opoly bisa membantu mereka dalam belajar untuk berbicara teks recount. Kata Kunci: Berbicara, English-Opoly, Permainan, Siswa Kelas 8 Abstract Speaking is considered as the most difficult skill in learning English. An early observation done in SMPN 1 Ngoro showed that the students were good in understanding the lesson, but they were hesitant to speak. They needed more relaxing atmosphere in learning English in the classroom. Speaking recount text can not be measured by one’s knowledge on generic structure only, but it should also be measured by practicing to express it. Therefore modified game like English-opoly is needed as a new medium to help the students speak recount text easily in a fun way. Because games create fun and relaxing atmosphere (Uberman, 1998). This study used R & D model by Borg and Gall to develop the conventional monopoly game to become English-opoly for the teaching of speaking recount text to the eighth graders. Besides, this study also investigated the students’ responses toward the implementation of the game developed. The expert validation showed that the game is appropriate for the students to help develop objectives of the study. This game also fulfills the criteria of a good game as teaching medium. Furthermore, data from observation and interview showed that most of the students gave positive response and agree that English-opoly is helpful for them in learning speaking Recount text. Keywords: Speaking, English-opoly, Game, Recount Text, Eighth graders INTRODUCTION One of the hardest aspects for the teacher to help the students with is learning to talk in the foreign language HYPERLINK ł "_ENREF_3" (Brown & Yule, 1983). It could be said that teaching speaking is challenging for most Indonesian students find it very difficult to speak in English. The difficulties to speak are caused by some reasons; the students' characteristic, the typical classroom activity, and the teacher's way of teaching. Junior High School Students are categorized as young learners who still love spending their time with friends and being trouble makers in the class. The years of early adolescents can be difficult, but they can also be an exciting time for them to learn HYPERLINK ł "_ENREF_5" (Casas, 2011). Therefore, students can be great learners if the teacher can engage them and involve them more in an interesting learning activity. However, in the practice of teaching speaking nowadays, the class does not provide an atmosphere which motivates the students to learn speaking; they are made-up to sit nicely in the classroom and listen to the teacher who knows everything and always be dominant in the classroom HYPERLINK ł "_ENREF_10" (Lestari, 1999). In addition, studying in a large class with limited time demotivate the students to practice speaking HYPERLINK ł "_ENREF_13" (Songsiri, 2012). Moreover, speaking, as the most difficult skill to learn, is taught in more limited time. Furthermore, most of the teachers still rely on textbooks as the primary teaching resource HYPERLINK ł "_ENREF_7" (Faridi, 2010). Likewise, the teacher uses most of the time to explain the lesson from textbook while the students are listening quietly. In Indonesia, the students are learning English on text based. One of the texts learnt in Junior High School especially in the 8th grade is the recount text. Traditionally, in learning speaking recount text, the students are provided with a generic structure which is aimed to guide them producing an oral recount text. However, it was found that even a clear generic structure is not enough to help them arrange a good recount text; they need a clearer instruction and also models or examples of recount text. In fact, explanation from the teacher is a typical activity which demotivates the students and gives less opportunity for them to practice speaking. They need a change in learning English to make them active in learning, understand the lesson clearly then finally apply their knowledge. This poor condition can be overcome by changing the way of teaching and reforming classroom activities which fit the students' characteristic; one of the ways is by creating relaxing atmosphere in the classroom so that the students will not be afraid of speaking in front of the classroom HYPERLINK ł "_ENREF_6" (Davies & Pearse, 2000). Based on the consideration, the students can practice speaking well if they are given relaxing and less-pressure opportunities. One of the ways to create relaxing and less-pressure atmosphere is applying fun yet educational media in the classroom. Media play important roles in teaching and learning process, they are used to entertain, to inform and to instruct HYPERLINK ł "_ENREF_11" (Locatis & Atkinson, 1984). In applying teaching media, some important considerations should be taken; the media should be enjoyable so that the students can forget the boredom of studying. It should also be able to help the teacher deliver the lesson and instruction to the students easily. The most important point is that if the media applied in the classroom are not suitable for the students, they may be bored and lose their interest to participate in the classroom HYPERLINK ł "_ENREF_8" (Harmer, 2007). Thus, the teacher needs a medium that is appropriate for the students and able to engage them to be active in practicing English. Among many kinds of media, games are considered as the best media to teach speaking English. It is so since games create fun and relaxing atmosphere HYPERLINK ł "_ENREF_14" (Uberman, 1998). Additionally, the students will try harder in games than other courses HYPERLINK ł "_ENREF_1" (Avedon & Smith, 1975). While students are playing the game, they try their best so that they can forget that they are actually studying; while in the same time they can get the knowledge. It could be said that game is an effective medium of instruction since it brings both fun and educational atmosphere. Hence, a game called English-opoly was developed to help the students learn speaking. English-opoly was the modified version of the conventional monopoly which was developed to become a medium in teaching speaking recount text. It is expected that by playing this game, the students could actively speak English and meet the objective of learning to speak recount text easily. Thus, some modifications were made so that the game suits the needs of the teaching and learning process. In English-opoly, a board, two dices, tokens, deed cards and chance cards are the properties to play the game. In the conventional monopoly's board, there are forty spaces with the name of countries in each block, while English-opoly board is divided into four blocks. There are six spaces in each block, and each space is called as the theme. Since English-opoly is a medium for speaking recount text, the theme of the board is holiday. Furthermore, the title of deed cards in the conventional monopoly is usually named as countries or cities, while in English-opoly, the deed cards consisted of incomplete sentences of orientation and events. Therefore, this research was intended to develop English-opoly for the teaching of speaking recount text to the 8th graders. Additionally, this research also investigated the students' responses toward the implementation of the game developed. METHOD This study used research and development method with qualitative approach. Research and Development (R & D) is a process used to develop new educational products which are systematically field tested, evaluated, and revised until they meet specific criteria of effectiveness HYPERLINK ł "_ENREF_2" (Borg & Gall, 1983). For the purpose of this study, all steps in Borg and Gall's R and D design were not fully taken. A modification of Borg and Gall's design are made. Research steps such as Dissemination and Implementation were left so that the steps taken in developing the English-opoly game were information collecting, planning, developing preliminary form of product, material and media expert validation, preliminary field testing, main product revision, main field testing, and final product revision. Since the research was intended to develop a new game as teaching media, media and material experts were involved to validate that the game is appropriate to be used as a medium of an instruction. The material expert for this study was an English teacher of a school in Jombang while the media expert in this research was a lecturer of Graphic Design Department of Surabaya State Uniersity. To develop the game, preliminary and main field tests were done. The field tests were conducted in SMP Negeri 1 Ngoro to know the students response toward the game. The sample of the population was taken randomly for this study. There were 8 students in the preliminary field test and 16 students in the main field test. The data of this study was collected using three instruments; a questionnaire, an observation checklist and interviews guidelines. The semi-structure questionnaire was used for both media expert and material expert. There were four aspects covered in the questionnaire; i.e. the suitability of the material to the students, the effect of the product towards the students, the applicability, the design and the language of the game. An observation checklist was included to the structure observation and was used to get the data of the second research question. There were some indicators in the checklist where the writer gave the tick (√) on them. They were about the appearance and the content of English-opoly game, and also students’ acts while playing this game. The interview was done to the students and the teacher. The interview for students was aimed to know the students' responses toward this game while the interview for the teacher was aimed to know whether the game fitted the students. In conducting this study, a qualitative data analysis was used. The data was analyzed based on the order of data collection technique. First, the data gained from the questionnaire filled by the experts were analyzed to revise the product to be tested in main field. Second, the data got from observation checklist and interviews were analyzed too. After the main field testing was done, the data from experts' answers on the questionnaire, the result of the interview, and the observation checklist were analyzed. RESULTS Based on the data obtained from the questionnaire given to the material expert, it was revealed that the students were considered very familiar with the conventional monopoly game. That is why it was answered that the students understood the rules of English-opoly, for it was clearly written and it was not very different from the conventional monopoly rules. Furthermore, the material used in English-opoly was really appropriate with the objectives of learning speaking English for the eighth graders. She agreed that the material used in the game was also not too appropriate for the students. In addition, she also mentioned that the material of the recount text was also interesting for the students. Besides, she undoubted that this game would be able to help the students understand recount text. Moreover, this game would be able to engage the students to be more active and fluent in speaking English. Generally, the modification done in the conventional monopoly to be English-opoly was really good according to her since it was very engaging and she believed it made the students more enthusiastic in learning. The review from media experts contained the judgment of the design and appearance of the product developed. According to the media expert, the students were familiar with the conventional Monopoly game. Conventional monopoly game was the monopoly game that was usually found in toy stores and played by children and adolescences. This English-opoly game which was modified from the conventional monopoly game was also expected to be easy for the eighth graders. However, he suggested that some modifications on the design of the board, the fonts, and packaging. The colors of English-opoly board and cards were considered to be interesting for the students. The text on the board and the cards were good, but he thought that the draft should be modified since there were some unclear text; i.e. the texts on the corner of the board. The expert also suggested the logo of the product should be redesigned in order that became the centre of interest. The design of the draft product considered less interesting for some of the students. The most important thing which became the problem for him was the packaging. He did not like the package which was made from plain thick paper. Thus the packaging needed to be redesigned by adding some illustration or pictures on it. However, the material used for English-opoly game such as the papers were appropriate. Although there were many colors and pictures, the media expert agreed it would not bother students' focus on the lesson. Overall, English-opoly was able to increase students' enthusiasm in learning and it was appropriate to become a media in learning English in the class, however there were some revision for the draft to make the product better and suitable. In preliminary field testing, the data were obtained from the observation and the interview to the students. From the observation, it was known that the students well understood how to play the game. However there were some students who did not actively involved in the activity. The teacher also did not find any difficulty in implementing the game in the class. But then, the teacher found that it was ineffective if a board of English-opoly was played by 8 students. She suggested that a board of English-opoly was played by 4 students only. After the field test, 8 questions were addressed to 8 students. The interview was aimed to know the students' responses toward English-opoly game. The first question was intended to know the students' familiarity toward monopoly. All subjects stated that they knew conventional monopoly well. Five of eight students considered that English-opoly was easy to play while three students found difficulties such as in reading the chance cards, working together with friends and finding the deed cards. From the interview it was known that all subjects had understood the rules of English-opoly. Moreover, six of eight students said that the color and design of the board were interesting, but two of the students said that the color was less bright. The fifth question meant to know the students' opinion about the whole game. Most of them said that playing English-opoly was fun and they could forget that they were studying. The sixth, seventh and eighth questions were intended to know the interest of the students toward the game. It was known that eight or all of the students felt happy after playing English-opoly. They also thought that the game was very helpful for them to learn speaking and recount text so they all wanted to play it again. Previously, in English-opoly rules, it was written that the students had to collect a deed card consisted of orientation and three or four deed cards of events. Then the material expert suggested changing the rule for saving the time. So the students had to collect 4 cards, they were a deed card of orientation, 2 cards of events and a card of reorientation. Next, the changing also had to be done to the deed cards. Some deed cards were considered to be unclear for the students. Thus, some information should be added to the cards. For example, the card that was written "go to Bedugul" had to be changed to become "go to Bedugul lake" because not all students knew what Bedugul was. The material expert also suggested adding pictures to the deed cards. It was believed to help the students arrange the recount text. Also, the prior design of the English-opoly board was very simple. Then, the media expert suggested redesigning the board so it looked more attractive. The illustration should be added on the centre of the board. Besides, the fonts of the word "English-opoly" should be changed to make it became the logo and the centre of interest of the product. In the second field test, it was acknowledged that the students found that it was easy to play English-opoly. The teacher also seemed more easily implemented the game and managed the class since the rule of playing the game was changed. Beside the data got from the observation, in the second field test, the data were gained from the interview to the students and the teacher. The first interview which consisted of 8 questions was addressed to 16 students. The interview aimed to know the students' response toward the game. The interview result of the second field test showed that all of the 16 students had known monopoly well; however there were a student found that it was difficult to play English-opoly because she could not easily collect the deed cards. The next questions dealt with the feature the game such as the board design and the color. All of the 16 students liked the design and the color of the board. To know how the game affected the students, the sixth, seventh and eighth question were delivered. Then it was known that all students considered that the game was engaging, fun and helpful. However, there was a student said that she would not play the game anymore because she felt bored, while 15 students were willing to play the game more. After interviewing the students, the researcher asked the teacher 8 questions to know the teachers responses toward the implementation of the game. The interview also aimed to get more suggestion to revise the product and to know the material appropriateness during the first and the second testing. According to the teacher's answer of the first question, it was known that almost all students had been very familiar with the conventional monopoly game. He considered that the modification of the conventional monopoly game to become English-opoly was quite good idea since it could make the students become more enthusiastic in learning English. Then, when the teacher was asked about the difficulties of the implementation of the game, he said that the only problem found was when the teacher organized the students to be grouped in the first field test. But in the second field test it was easier to organize the class because the students only needed to turn around their seats to be in a group of 4. Moreover, when the teacher was asked whether there was something that had to be added in the game, he said that there was nothing to be added because the game had been appropriate for the students, especially about things related to the material and also the age of the students. Related to the implementation, the teacher suggested that the time should be longer than 15 minutes to play the game. He also gave some suggestion that it would better to have 4 students in group as in the second field-test rather than 8 students in a group as in the first field-test. Related to the teacher's response toward the implementation of the game, there were two things to be revised. They were the time allocation and the group organization. The time allocation was revised to become 20 minutes to play the game. Then, to make it easier for the teacher to organize the class, the group organization was decided to be 4 students in a group for each board of English-opoly. After doing the main field test, to make a best product, the questionnaire was given to the media expert for the second time because at the first questionnaire, it showed that the media was very far from criteria of effectiveness. On the second questionnaire, media expert suggested that the size of the package should be smaller. In result, the board has to be flipped 2 times before being put in the smaller box or package. Then the material for the package should be changed to duplex paper so that it could be stronger and safer to keep the board, cards, tokens and dices. However, generally the whole design and media had been improved and good. Thus he stated that English-opoly could be used as media to teach English after the revision of the package size. After revising English-opoly based on the experts' review and the field tests, the final product of English-opoly was gained. The appearance of the final product of the board and package of English-opoly could be seen in the picture below Picture 1 Final product of English-opoly In the final product of English-opoly game, some features were revised and changed. The pictures on the board were brighter, the design illustration of whole board was much better and the fonts were clearer than it was in the preliminary design. Generally, the final product had had good combination between color, font and picture. The material used for the game was also changed into better quality paper. Moreover the package was now simpler because it was smaller. The rule of the game was also added to the package, so the students could read the rule themselves. DISCUSSION This study was intended to create English-opoly game by developing the conventional monopoly game to become English-opoly for the teaching of speaking recount text to the 8th graders and to investigate the students' responses toward the implementation of the game developed. Carrier HYPERLINK ł "_ENREF_4" (1980) believed that when the level of the game fit the students' language level, they can learn English more from the game. According to the judgment of the material expert, the material used in English-opoly suited the learning objectives of the eighth graders. Data gained from the questionnaire to the material expert said that the language used in the game also fitted students' comprehension. Thus, English-opoly was appropriate to be used as media to teach the eighth graders. Based on the responses of the students through the interview, the students found out that the game was enjoyable and so they had fun during playing the game. Furthermore, the game was also educational and English promoting since the students agreed that they could easily produce recount text and they had more time to practice speaking English by presenting it orally in front of their friends after playing the game. Hence, based on the positive responses from the students, it could be inferred that the game was applicable to teach speaking recount text based on the fact that English-opoly fulfilled five criteria; engaging, easy to use enjoyable, educational, English promoting HYPERLINK ł "_ENREF_9" (Hill, Sumarniningsih, & Lestari, 2013). Additionally, the result of the observation during the tests and the interview after the first and the second field test had shown that while the students were playing the game, they enjoyed it and felt relax. It was in line with the theory that games create a fun and relaxing atmosphere HYPERLINK ł "_ENREF_14" (Uberman, 1998). Avedon and Smith (1975) believed that the students always try harder in games than other courses. This condition happened during the observation; it was known that the students were very enthusiastic. They tried hard to collect the deed cards to make recount text when playing the game. After playing the game, the students had to express their recount text in front of their friends, and the relaxing atmosphere brought by the game made the students easy to prepare what they were going say in the presentation. Therefore, good preparation in a relaxing atmosphere made the students confident in presenting their text. It proved the theory that game is designed to foster creativity, develop fluency, and improve public speaking skills HYPERLINK ł "_ENREF_12" (Rooyackers, 2002